Relative dose distribution in gamma knife treatment near tissue inhomogeneties - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2005)
The primary goal in this study was to investigate 3-D dose distribution, near the areas of tissue inhomogeneities, in Gamma Knife Radiosurgery with the gel dosimetry. The spherical glass balloon of a diameter of 16 cm filled with the gel forms the homogeneous phantom; and an identical balloon with two corks placed on each side to represent the air cavities forms the inhomogeneous phantom. Dose calibration is performed by irradiating vials at known doses and then utilizing the R2-dose calibration curve. Stereotactic frames and fudicial markers were attached to the phantoms for MR scanning and image processing. Dose distributions from a single shot, using all 201 Cobalt sources, delivered to a known point with identical coordinates, are calculated both in homogeneous and inhomogeneous gel phantoms. In the aspect of dosimetrical quality control, the Gamma Knife planning system predicted dose distribution is compared with the experimental results. In the homogeneous phantom, the gel dosimetry calculated dose distribution is in good agreement with the GammaPlan predicted dose distribution. However, with the inhomogeneous phantom, the dose distribution is spatially different and significant differences in dose levels are observed. © 2005 IEEE.
Keywords: Gamma knife; Polymer gel dosimetry; Stereotactic radiosurgery; Tissue inhomogeneity